THE LIPID ACCUMULATION PRODUCT INDEX AS AN ALTERNATIVE BIOMARKER FOR EARLY DETECTION OF METABOLIC SYNDROME: A NARRATIVE REVIEW - Alya Ayu Alvitananda; Adriyan Pramono; Etika Ratna Noer (Journal of Nutrition College, 2026)
ABSTRACTBackground: Metabolic syndrome (MetS) is a cluster of metabolic disorders that increases the risk of cardiovascular disease and type 2 diabetes. Early detection is crucial, especially in developing countries with limited healthcare services and infrastructure. The lipid accumulation product (LAP) index offers a simple, affordable, and accurate alternative biomarker because it reflects visceral fat accumulation as a significant risk factor for MetS.Objective: This review aims to evaluate the potential of the LAP index as an alternative biomarker for MetS screening through a narrative review of various global epidemiological studies.Methods: This study employs a narrative review approach, incorporating theoretical analysis and data from international articles. The search was conducted across several databases, including PubMed, ScienceDirect, and Google Scholar. Data were searched from peer-reviewed articles published between 2016 and 2025 using several selected keywords, including lipid accumulation product, metabolic syndrome, biomarkers, visceral fat, and insulin resistance.Results: A review of 10 studies showed that the LAP index had an area under the curve (AUC) value > 0.850 in most studies, with sensitivity (Sn) and specificity (Sp) generally exceeding 80%. The LAP index also demonstrated better or comparable diagnostic performance to other biomarkers. In addition to its good statistical validity, this index also excels in terms of physiology and practicality.Conclusion: The LAP index has the potential to serve as an efficient, affordable, and applicable biomarker for screening MetS based on various global epidemiological studies, and supports more targeted prevention and lifestyle interventions in at-risk individuals.Keywords: Lipid accumulation product; metabolic syndrome; biomarker; visceral fat; insulin resistance